PENGARUH JUS BUAH TERUNG BELANDA (Solanum betaceum Cav.) TERHADAP KADAR HEMOGLOBIN PADA MAHASISWI KEPERAWATAN FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH BENGKULU - Larra Fredrika; Lussyefrida Yanti (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
Anemia is a condition in which the concentration of hemoglobin or the number of red blood cells is below normal. The occurrence of anemia can be caused by damage to blood cells as a result of strenuous exercise which generally causes loss of iron (Fe) so that hemoglobin (Hb) levels decrease. This study aims to determine the effect of Dutch eggplant juice on hemoglobin (Hb) levels in nursing students, Faculty of Health Sciences, University of Muhammadiyah Bengkulu. This study uses an experimental method, using a pre-experimental design with a pretest-posttest design. The results showed that there was a difference in hemoglobin (Hb) levels before and after being given the Dutch eggplant juice with p value = 0.000 (<0.05). It can be concluded that there is an effect of Dutch eggplant juice on hemoglobin (Hb) levels in nursing students, Faculty of Health, University of Muhammadiyah Bengkulu.Keywords: Anemia, hemoglobin, dutch eggplant juice